Nitrous Oxide Abuse and Vitamin B12 Action in a 20-Year-Old Woman: A Case Report. Issue 4 (20th November 2015) - Duque, Miriam Andrea; Kresak, Jesse L.; Falchook, Adam; Harris, Neil S.
Abstract : Herein, we report a case of a 20-year-old (ethnicity not reported) woman with a history of nitrous oxide abuse and clinical symptoms consistent with spinal cord subacute combined degeneration with associated low serum concentrations of vitamin B12, elevated methylmalonic acid levels, and radiologic evidence of demyelination of the dorsal region of the spinal column. The health of the patient improved dramatically with B12 supplementation. In this case, we discuss the interaction of nitrous oxide with the enzymatic pathways involved in the biochemistry of vitamin B12